1995
DOI: 10.1002/ana.410380207
|View full text |Cite
|
Sign up to set email alerts
|

Leber's hereditary optic neuropathy plus dystonia is caused by a mitochondrial DNA point mutation

Abstract: A novel point mutation in the ND6 subunit of complex I at position 14,459 of the mitochondrial DNA (MTND6*LDY T14459A) was identified as a candidate mutation for the highly tissue-specific disease. Leber's hereditary optic neuropathy plus dystonia. Since the MTND6*LDYT14459A mutation was identified in a single family, other pedigrees with the mutation are needed to confirm its association with the disease. Clinical, biochemical, and genetic characterization is reported in two additional pedigrees. Leber's here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
63
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 15 publications
2
63
0
Order By: Relevance
“…For example, mutations in MT-ND1 and MT-ND4 can cause Leber hereditary optic neuropathy (LHON), a disease characterized by bilateral, painless central vision loss in early to late adulthood resulting from the specific degeneration of retinal ganglion cells in the optic nerve [40]. However, these same mutations can also be associated with more severe symptoms, including dystonia and short stature [41][42][43].…”
Section: Mitochondrial Diseasementioning
confidence: 99%
“…For example, mutations in MT-ND1 and MT-ND4 can cause Leber hereditary optic neuropathy (LHON), a disease characterized by bilateral, painless central vision loss in early to late adulthood resulting from the specific degeneration of retinal ganglion cells in the optic nerve [40]. However, these same mutations can also be associated with more severe symptoms, including dystonia and short stature [41][42][43].…”
Section: Mitochondrial Diseasementioning
confidence: 99%
“…Classical LHON is presenting with acute to subacute central vision loss, but pedigrees in which both LHON and dystonia are segregating, due to point mutations in the gene encoding ND6, have been reported. 8,9 Here we report a 6-year-old patient with the typical clinical features of MELAS and no signs of LHON, who harbours a novel mitochondrial point mutation in the gene encoding the ND6 subunit of NADH:ubiquinone oxidoreductase (complex I of the respiratory chain).…”
Section: Introductionmentioning
confidence: 98%
“…Molecular analysis of this pedigree revealed that both the LHON and the dystonia were the result of a mutation in the mtDNA complex I gene MTND6, resulting in the conversion of the highly conserved alanine codon at position 72 to a valine (7). This same mutation in different families can be associated with either LHON or dystonia or both (11). Cells containing this mutation have a 55% reduction in respiratory complex I activity, which can be transferred from one cell to another along with the mtDNA via the cytoplasmic (cybrid) transfer technique (12).…”
mentioning
confidence: 99%